2015
DOI: 10.13189/ujph.2015.030405
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Uptake and Utilization of National Hospital Insurance Fund Medical Cover by People in the Informal Sector in Kakamega County, Kenya

Abstract: Low and middle-income countries have extended state sponsored Social Health Insurance (SHI) to people outside the formal sector to enhance access to healthcare. However, in spite of the relatively low costs of signing up and the benefits offered by SHIs, uptake rates are very low among the informal sector populations. The objective of this study was to investigate factors affecting participation of people in the informal sector in the National Hospital Insurance Fund (NHIF) scheme in Kakamega County, Kenya. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A similar study done in Kakamega country in Western Kenya with 400 participant showed that people with higher income are likely to register in the scheme (OR 2.21 with 95% CI:1.07 to 4.03) which reflects similarity with our study. 9 My study showed that the source of information plays a significant role in the utilization of the scheme (0.025). Most of the participant had heard about the scheme from their family members (53.2%) yet this result contrast with a cross sectional study done by Macharia et al that showed no significant association among source of information (0.770).…”
Section: Resultsmentioning
confidence: 99%
“…A similar study done in Kakamega country in Western Kenya with 400 participant showed that people with higher income are likely to register in the scheme (OR 2.21 with 95% CI:1.07 to 4.03) which reflects similarity with our study. 9 My study showed that the source of information plays a significant role in the utilization of the scheme (0.025). Most of the participant had heard about the scheme from their family members (53.2%) yet this result contrast with a cross sectional study done by Macharia et al that showed no significant association among source of information (0.770).…”
Section: Resultsmentioning
confidence: 99%
“…NHIF uptake in the four counties was similar, ranging from only 21-25%. This is lower than the uptake rates described in Kakamega, Muranga and amongst women in central Kenya likely because our study covered largely a peri-urban and very rural population (11,23).…”
Section: Discussionmentioning
confidence: 62%
“…Importantly, that study did dig deeper into the actual kind of knowledge participants had on NHIF and found that only 34% had the correct knowledge. It is therefore possible that despite the high rates of awareness we recorded , the actual knowledge held may not be correct (23).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(22) For marital status, some of the studies have shown that those who are married are likely to enroll in NHIF because of the nancial support they have from their partners and for singles register low enrollment on NHIF. (23) There is a need to improve health service delivery and nancing yet there is paucity of data on NHIF awareness uptake and factors affecting its uptake in western Kenya. We set out to ll this gap.…”
Section: Health Statusmentioning
confidence: 99%